Antenatal umbilical coiling index in gestational diabetes mellitus and non-gestational diabetes pregnancy - Laily Najafi; Mohammad E. Khamseh; Maryam Kashanian; Ladan Younesi; Azadeh Abedini; Ameneh Ebrahim Valojerdi; Zahra Amoei; Elmira Nouri Khashe Heiran; Abbas Ali Keshtkar; Mojtaba Malek (Taiwanese Journal of Obstetrics & Gynecology, 2018)
Objective: Umbilical cord abnormalities increase fetal morbidity and mortality. This study was designed to compare antenatal umbilical coiling index (aUCI) in gestational diabetes mellitus (GDM) and non-gestational diabetes mellitus (non-GDM) pregnancy, considering uncertainties about the best time to perform antenatal ultrasonography scan. Materials and Methods: In this prospective study, 246 parturients were included, 123 with GDM and 123 with non-GDM pregnancy. Gestational diabetes was confirmed at 24–28 weeks of gestation (WG) using one-step strategy. An anatomical ultrasound survey of placenta and umbilical cord was performed at 18–23 as well as 37–41 weeks of gestational age. Results: At 18–23 WG, the frequency distribution (10th, 90th percentiles, mean ± SD) of the aUCI in the GDM and non-GDM groups were (0.13,0.66,0.32 ± 0.19) and (0.18,0.74, 0.4 ± 0.31) respectively. These values were (0.12,0.4, 0.25 ± 0.11) in the GDM group at 37–41 WG and (0.17,0.43, 0.29 ± 0.11) in the non-GDM group. A significant relationship was detected between UCI value and GDM/non-GDM groups at both antenatal evaluations (18–23 WG; P = 0.002, 37–41WG; P < 0.001). A significant association at 18–23 WG was found between GDM/non-GDM groups and aUCI categorization (hypocoiling <10th, normocoiling 10th–90th and hypercoiling >90th) (P = 0.001). However, hypocoiling were significantly more frequent in GDM than non-GDM in both antenatal evaluations (P < 0.001, P = 0.006). Conclusion: Antenatal UCI in pregnancy complicated by GDM were lower in comparison with non-GDM pregnancy. The most abnormal pattern of coiling in gestational diabetes was hypocoiling in both trimesters. In addition, 18–23 WG is the best time to perform ultrasound scan to detect aUCI and umbilical cord pattern. Keywords: Antenatal, Gestational diabetes mellitus, 75-g oral glucose tolerance test, Ultrasonography, Umbilical coiling index